The Rhetoric of Violence, Religion, and Purity in India’s Cow Protection Movement - Gittinger, Juli L. (Journal of religion and violence, 2017)
In India there has been a recent increase in violence and intolerance towards people who eat beef. While India has a fairly wide Cow Protection Act that bars the slaughter of female cows and calves, many areas have permitted slaughter of bulls and bullocks for centuries. Hindu religion has no doctrinal proscriptions against the consumption of beef in particular, although it has borrowed heavily from Jainism in the last century, arguing that the concept of ahimsa (nonviolence) forbids such slaughter and consumption of beef. Violence is exacted upon those who would dare eat beef—notably Muslims and lower castes—further politicizing the issue. This paper explores the various claims and legitimations of violence regarding the tradition of abstaining from beef. These include arguments of religious purity, racial biases, caste, and cultural arguments which have been put forth in defense of or in condemnation of beef-eaters. I argue that, in the case of such regulations of "authentic" Hindu traditions (like the sanctity of the cow), purity concerns are directly tied to Hindu nationalist ideologies.